EFEK EKSTRAK BUNGA KENANGA (Canangium odoratum) SEBAGAI AGONIS PADA RESEPTOR ADRENERGIK-β ββ βDI PARU TERPISAH MARMUT (Cavia porcellus) - Charisti, Pherenice; Loekito, Retno M; Karyono, Setyawati S (Jurnal Kedokteran Brawijaya, 2004)
The cananga flower (Canangium odoratum) is one of the herbal medicine used for asthma bronchiale. Cananga extract have been proved to relax the isolated guinea pig’s tracheal  and bronchus smooth muscle. The relaxation of the tracheal smooth muscle could be inhibited by propanolol 10-9M, however propanolol 10-9M could not inhibit the relaxation of the bronchialsmooth muscle. Therefore the objective of this study is to investigate the effect of cananga extract on relaxation of isolated  guinea pig’s lung strip through  β-adrenergic receptor. Three different dose of propranolol was used as  β-adrenergic receptor antagonist. This study was an experimental research using guinea pig’s isolated lung strip. The control group was given histamine and cananga extract. The first group of treatment was administrated histamine, propanolol 10-9M and cananga extract. The second group of treatment was given histamine, propanolol 10-8M and cananga extract. The third group of treatmentwas given histamine, propanolol 10-7M and cananga extract. The results of this study showed that cananga extract caused relaxation of lung strip and there was a reduction in the relaxation of lung strip after administration of propanolol. The reduction in relaxation lung strip caused by propranolol inhibition was found to be significant using regression testing. In conclusion, cananga extract works as a partial agonist to β-adrenergic receptors in bronchial smooth muscle of guinea pigs since the dosage response curve showed shift to the right but it was not paralel. Keyword :cananga extract, relaxation of lung strip, β-adrenergic receptor.